A new three-dimensional parametric FVDAM for investigating the effective elastic moduli of particle-reinforced composites with interphase. Issue 22 (17th November 2019) - Ye, Junjie; Hong, Yun; Cai, Heng; Wang, Yongkun; Zhai, Zhi; Shi, Baoquan
ABSTRACT: In recent years, the micromechanics model plays an important role in investigating the mechanical properties for particle-reinforced composite (PRC) materials. In this article, through discretizing the representative volume element (RVE) with eight-node hexahedral isoparametric elements, as well as expressing the higher-order displacement functions as the function of surface-averaged displacements for the subcell, a new parametric micromechanical model is presented to investigate the elastic constant variations of the three-dimensional PRC. For validating the proposed method, the finite element method (FEM) is employed for solving the PRC without consideration of interphase. The calculated results by employing the FEM show a good consistency with the proposed micromechanical method. Furthermore, interphase thickness, as well as interphase modulus effect on elastic constant are further predicted and discussed.